Digital cultures of political participation: Internet memes and the discursive delegitimization of the 2016 U.S Presidential candidates. (April 2017) - Ross, Andrew S.; Rivers, Damian J.
Abstract: Internet memes are a contemporary phenomenon situated at the nexus of language, society, and digital communication, and represent a relatively new form of participatory culture that can offer certain demographics an opportunity for political expression, engagement and participation which otherwise might not have been accessible. This article adopts a discourse analytical perspective to examine the visual-discursive features of Internet memes in relation to the candidates for the 2016 U.S presidential election – Donald Trump and Hillary Clinton. Specifically, memes are analyzed in line with Van Leeuwen׳s (2007) framework for the analysis of legitimizing discourse in relation to how they de -legitimize. That is, the focus is on how memes attempt to create a negative view of the candidates and reduce their legitimacy as presidential candidates. The analysis reveals that the (de)legitimization strategies of authorization, moral evaluation, rationalization and mythopoesis are all evident within Internet memes. Highlights: Memes used as delegitmization are presented. The delegitimization strategies of authorization, moral evaluation, rationalization and mythopoeisis are highlighted. Internet memes are shown to be an effective mode of political participation.